2017
DOI: 10.1016/j.ydbio.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Development or disease: duality of the mitochondrial permeability transition pore

Abstract: Mitochondria is not only a dynamic organelle that produces ATP, but is also an important contributor to cell functions in both development and cell death processes. These paradoxical functions of mitochondria are partially regulated by the mitochondrial permeability transition pore (mPTP), a high-conductance channel that can induce loss of mitochondrial membrane potential, impairment of cellular calcium homeostasis, oxidative stress, and a decrease in ATP production upon pathological activation. Interestingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 102 publications
1
91
0
Order By: Relevance
“…However, the depletion of Mfn2 attenuated cardiac cell death in response to ischaemia-reperfusion injury and reduced the potential to undergo calcium-dependent mitochondrial permeability transition (MPT) (Papanicolaou et al, 2011). MPT is a tightly regulated process that is mediated by mitochondrial permeability transition pore (MPTP), a high-conductance, calcium-sensitive channel that induces mitochondrial depolarization and dysfunction upon opening (Haworth & Hunter, 1980;Perez & Quintanilla, 2017). MPTP is an important determinant of myocyte loss, especially during ischaemia and reperfusion injury (Di Lisa & Bernardi, 2006;Baines, 2009;Halestrap, 2009).…”
Section: Tissue-specific Functions Of the Mitofusinsmentioning
confidence: 99%
“…However, the depletion of Mfn2 attenuated cardiac cell death in response to ischaemia-reperfusion injury and reduced the potential to undergo calcium-dependent mitochondrial permeability transition (MPT) (Papanicolaou et al, 2011). MPT is a tightly regulated process that is mediated by mitochondrial permeability transition pore (MPTP), a high-conductance, calcium-sensitive channel that induces mitochondrial depolarization and dysfunction upon opening (Haworth & Hunter, 1980;Perez & Quintanilla, 2017). MPTP is an important determinant of myocyte loss, especially during ischaemia and reperfusion injury (Di Lisa & Bernardi, 2006;Baines, 2009;Halestrap, 2009).…”
Section: Tissue-specific Functions Of the Mitofusinsmentioning
confidence: 99%
“…The ultrastructural damage of mitochondria in the ECs exposed to PM 2.5 was observed by transmission electron microscopy. As shown in (Kang et al, 2017;Pérez & Quintanilla, 2017). The ΔΨm loss in ECs (Figure 4) might be attributed to the direct interaction between PM 2.5 and the mitochondrion, leading to the physical damage in mitochondria and regulation of mPTPs to depolarize ΔΨm ( Figure 5).…”
Section: Discussionmentioning
confidence: 87%
“…The altered expressions of fission or fusion proteins further reflect PM 2.5 ‐induced mitochondrial damage. It was demonstrated that the induction of mitochondrial damage includes changes in ΔΨm and mPTP openings (Kang et al, ; Pérez & Quintanilla, ). The ΔΨm loss in ECs (Figure ) might be attributed to the direct interaction between PM 2.5 and the mitochondrion, leading to the physical damage in mitochondria and regulation of mPTPs to depolarize ΔΨm (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Among mechanisms involved in mitochondrial pathogenesis is the opening of the mitochondrial permeability transition pore (MPTP), which results in uncoupling of the mitochondrial respiratory chain, impaired ATP synthesis, and eventually mitochondrial swelling and cell death (Kwong & Molkentin, 2015;Perez & Quintanilla, 2017). The exact molecular identity of this complex has not yet been well defined and is the subject of intense debate although the molecular structure of MPTP includes the volt-dependent anion channel (VDAC), the adenine nucleotide translocator (ANT), and cyclophilin D, among other possible components that include the F1F0 ATP synthase for the pore-forming component (Bernardi & Di Lisa, 2015;Kwong & Molkentin, 2015).…”
Section: Discussionmentioning
confidence: 99%